THE ROLE OF WHITE CELL COUNT AND C-REACTIVE PROTEIN IN THE DIAGNOSIS OF ACUTE APPENDICITIS - Khan, MN; Davie, E; Irshad, K (Journal of Ayub Medical College Abbottabad, 2004)
Background: Despite recent advances in diagnostic medicine, the diagnosis of appendicitis is still doubtful in a number of cases. Majority of the clinicians rely on their clinical examination strengthened by the laboratory tests. This study was carried out to find out the specificity and sensitivity of white cell count (WCC) and C-Reactive Protein (CRP) in diagnosing appendicitis in patients presenting with right iliac fossa pain. Methods: A total of 259 patients were included in this study that presented in the hospital with acute right iliac fossa pain and later on operated and had appendicectomy. The histopathology data was collected to find out the frequency of negative appendicectomy. According to the histopathology reports these patients were grouped into three sub-groups as normal appendix, inflamed appendix or perforated/gangrenous appendix. A record was kept of the WCC and CRP levels of these patients on admission. Results: A total of 259 patients were included in this study and out of them 37 had a normal appendix giving an over all negative appendicectomy rate of 14.3%. Out of these 11 were male and 26 were female, male to female ratio being 1:2.3. The age range was 12-73 with a median age of 24. Among the 222 patients who had appendicitis, 96 had a ruptured /perforated appendix and 126 had an inflamed appendix. Over all the WCC was elevated in 185 patients and CRP was elevated in 168 cases. The cut off value for white cell count was 11 x 106 / L. The C reactive protein levels were calculated by immunoturbidimetric test and the cut off value was taken as 1.7mg/dl. The sensitivity and specificity of WCC in this study was 83% and 62.1 % and that for CRP was 75.6% and 83.7 %. Conclusion: Both the inflammatory markers i.e. WCC and C-reactive protein can be helpful in the diagnosis, when measured together as this increases their positive predictive value. Key words: appendicitis, white cell count, C reactive protein